2012
DOI: 10.3389/fncir.2012.00057
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and morphology of nitrergic neurons across functional domains of the rat primary somatosensory cortex

Abstract: The rat primary somatosensory cortex (S1) is remarkable for its conspicuous vertical compartmentalization in barrels and septal columns, which are additionally stratified in horizontal layers. Whereas excitatory neurons from each of these compartments perform different types of processing, the role of interneurons is much less clear. Among the numerous types of GABAergic interneurons, those producing nitric oxide (NO) are especially puzzling, since this gaseous messenger can modulate neural activity, synaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
20
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 69 publications
5
20
2
Order By: Relevance
“…The particularly complex roles of NO interneurons in the control of blood perfusion is extensively reviewed by (Duchemin et al, 2012) as an introduction to this section. As a first step in the understanding of their neurovascular functions, the anatomical relationships of type I interneurons with blood vessels is described in the rat cortical gray matter (Nogueira-Campos et al, 2012) and monkey white matter (Rockland and Nayyar, 2012) confirming and extending previous findings (Cauli et al, 2004). Stimulation of 5HT3A receptors expressed by type II NO interneurons and other discrete subpopulations of interneurons (Perrenoud et al, 2012b) leads to both NO-mediated vasodilations and NPYmediated vasoconstrictions.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The particularly complex roles of NO interneurons in the control of blood perfusion is extensively reviewed by (Duchemin et al, 2012) as an introduction to this section. As a first step in the understanding of their neurovascular functions, the anatomical relationships of type I interneurons with blood vessels is described in the rat cortical gray matter (Nogueira-Campos et al, 2012) and monkey white matter (Rockland and Nayyar, 2012) confirming and extending previous findings (Cauli et al, 2004). Stimulation of 5HT3A receptors expressed by type II NO interneurons and other discrete subpopulations of interneurons (Perrenoud et al, 2012b) leads to both NO-mediated vasodilations and NPYmediated vasoconstrictions.…”
supporting
confidence: 57%
“…This issue was revaluated in the whisker-to-barrel cortex by using NADPH-diaphorase histochemistry (Nogueira-Campos et al, 2012) revealing that type I neurons were enriched in deep layers whereas type II NO interneurons were particularly dense in superficial layers. Consistently, using a combination of patchclamp recordings, single cell RT-PCR and immunocytochemistry (Perrenoud et al, 2012a) disclosed that type I neurons were predominantly located in deeper layers and largely co-expressed somatostatin while type II neurons were concentrated in layers II/III and VI and heterogeneous at the molecular level.…”
mentioning
confidence: 99%
“…In conclusion, data provided by Nogueira-Campos et al (2012) offer new insights about the organization of interneuron circuitry across rat's S1. A further quantification of NADPH-d neuronal morphology in non-primary/association areas may contribute to a more complete notion of cortical differences in the inhibitory circuitry.…”
mentioning
confidence: 74%
“…In this context, a comprehensive work published by Nogueira-Campos et al (2012) in Frontiers in Neural Circuits contributes to cover this gap. In that study the authors evaluated the entire population of NADPH-d neurons found across rat's S1 in order to quantify the distribution of these cells throughout all body's representation and also evaluate the morphological aspects and relationship of these neurons with barrels and septal regions.…”
mentioning
confidence: 99%
“…More than 8000 additional neurons from recent publications are already in the processing pipeline for future releases, including individual archives of more than 2000 reconstructions each from studies in culture 16 and in vitro 17 . We typically identify more than one thousand new reconstructions every month through systematic literature searches and we receive several hundred of those upon request for public sharing in the same time span.…”
Section: Future Implicationsmentioning
confidence: 99%